Combination Therapy in Laryngopharyngeal Reflux - Ahmad, Raies; Saraf, Aditiya; Kishore, Kamal; Gupta, Nitika (International Journal of Innovative Research in Medical Science, 2020)
AIMS & OBJECTIVES- to evaluate response of combination of b.i.d(twice daily) PPI(Proton pump inhibitors) plus nocturnal H2RAs (H-2 Receptor antagonists) in laryngopharyngeal reflux disease. MATERIAL & METHODS- The present study was conducted on 100 patients between age group of 25-70 years attending ENT OPD of SMGS Hospital, GMC Jammu during a time period of November 2017 to September 2019.Inclusion criteria for our study were patients with symptoms of GERD (both esophageal and extraesophageal). Exclusion criteria were patients other associated gastrointestinal complaints, patients suffering from URTI and patients having symptoms less than a month.Patients were prescribed acid suppression therapy consisting of twice daily dose of PPI (Omeprazole 20 mg) plus bed time H2RA (Rantidine 150 mg) for four months and reviewed after every 15 days. RESULTS- Out of 100 patients, 71% patients showed improvement symptomatically at the end of four months and laryngeal findings resolved in 55% of patients. CONCLUSION- The combination of symptoms and laryngoscopic findings both show improvement with b.i.d PPIs. Additional nocturnal H2RA had minimal effect on response rate.